MODEL INTEGRATION (BIM) FOR MAINTENANCE BUILDING AS INFORMATION AND ACTION PLAN IN LAUNDRY LABORATORY AND KITCHEN LABORATORY OF PETRA SURABAYA CHRISTIAN UNIVERSITY - Ary Sunantiyo; Ronny Durrotun Nasihien (NAROTAMA UNIVERSITY, Indonesia, 2020)
Maintenance of each building along with every component and its facilities is needed to provide smooth and comfortable activities in the building. Often the building maintenance process/activity has not been able to run properly due to a lot of information such as maintenance records, work drawings (as-built drawings), types of assets, specifications, repair, and maintenance history that have not been recorded or stored properly. Most building maintenance systems currently only focus on existing information or records. The proposed information system is to utilize 3D modeling techniques namely BIM (Building Information Modeling), which through this BIM will be able to capture relevant information according to the data in the building. The technology used is the BIM (Building Information Modeling) technology using the SketchUp program. This method is by making a model of the building and its facilities. Modeling is done by giving visual data in 3D (three dimensions) to resemble the original object. The benefit of 3D (three-dimensional) modeling is that it provides clearer information because the visualization displayed is the same as the original object at the location, so just looking at the 3D model is quite the same as seeing the original object at the location. This research resulted in an information system in the form of three-dimensional visual model images that can be accessed easily. This concludes that an integrated Building Information Modeling (BIM) based system can provide useful functions in building maintenance quickly and accurately.